Effectiveness of Durian Fruit Seed Extract (Durio Zibethinus) on Kidney Function and Histopathology of Rats Induced by Wistar Streptozotocin - Virgoh, Livia; Suyono, Tan; Chiuman, Linda; Nurlaela, Lia; Kosasih, Michaela; lister , Clarissa (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia due to impaired insulin secretion or action. Diabetic nephropathy, a microvascular complication of type 2 DM, causes damage to kidney function due to progressive hyperglycemia. This study analyzed the potential of durian seed extract in reducing blood sugar levels (KGD) and improving kidney function and histopathological features in streptozotocin (STZ)-induced Wistar rats. Rats were divided into six groups: normal, positive control (STZ + metformin), negative control (STZ), and three treatment groups with durian seed extract doses of 150, 300, and 450 mg/kgBB. The extract was given for 14 days, followed by examination of kidney function and histopathology. The results showed that a dose of 450 mg/kgBB was most effective in reducing KGD, equivalent to metformin, which could improve kidney function and histopathology. Durian seed extract 450 mg/kgBB has the potential as an effective antidiabetic in reducing kidney damage.